2007
DOI: 10.1089/jir.2007.0003
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAntihydatic Action of IFN-γIs Dependent on the Nitric Oxide Pathway

Abstract: Hydatidosis is a widely endemic helminthic disease vectored in human by the larval stage of the metacestode Echinococcus granulosus. It is characterized by the long-term coexistence of chronic infection with detectable humoral and cellular responses against the macroparasite. Previous studies demonstrated interferon-gamma (IFN-gamma) and nitric oxide (NO) production (in vivo and in vitro) during hydatidosis. In this study, we tested the hypothesis that NO production after IFN-gamma induction may constitute a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…Controversially, some researchers reported NO-mediated immunosuppression following murine Echinococcus infection [131] and the high level of NO production during chronic infection, which contribute more to immunosuppression than to limitation of parasite growth [132]. Results indicated that IFN-ã mediated iNOS is induced as one of host defense mechanism against human E. granulosus infection [133]. Collectively, the data indicated that NO concentration correlate with IFN-γ levels, and overall suggest that their production together play a role in the host defense mechanisms in human hydatidosis [134].…”
Section: Echinoccocus Spmentioning
confidence: 99%
“…Controversially, some researchers reported NO-mediated immunosuppression following murine Echinococcus infection [131] and the high level of NO production during chronic infection, which contribute more to immunosuppression than to limitation of parasite growth [132]. Results indicated that IFN-ã mediated iNOS is induced as one of host defense mechanism against human E. granulosus infection [133]. Collectively, the data indicated that NO concentration correlate with IFN-γ levels, and overall suggest that their production together play a role in the host defense mechanisms in human hydatidosis [134].…”
Section: Echinoccocus Spmentioning
confidence: 99%
“…Our team has previously recognized interferon-gamma (IFN-γ) as the major mediator of host resistance against this parasite (Amri et al, 2007;Touil-Boukoffa et al, 1997. Production of reactive nitrogen intermediates including nitric oxide (NO) is thought to represent an important scolicidal mechanism of IFN-γ-activated human monocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Production of reactive nitrogen intermediates including nitric oxide (NO) is thought to represent an important scolicidal mechanism of IFN-γ-activated human monocytes. In fact, the inhibition of NOS2 (inducible NO synthase) activity and expression by NOS inhibitor (L-NMMA) (Amri et al, 2007) and cytokines (IL-10 and IL-4) (Amri et al, 2009) led to decrease the parasite killing.…”
Section: Introductionmentioning
confidence: 99%
“…Effector mechanisms include neutrophils and macrophage activation, nitric oxide (NO), eosinophil cationic protein, complement, and antibodies (Virginio et al 2007;Amri et al 2007;Ferreira et al 2000a;Heath et al 1994;Jenkins et al 1990;Ramos et al 2006;Ferragut and Nieto 1996;Severi et al 1997;Zhang et al 2003b;Riley et al 1986;Dempster et al 1992). Around live intact cysts there is a remarkably scarce inflammatory reaction, as opposed to regressive cysts (Breijo et al 2008;Coltorti and Varela-Diaz 1974;Marco et al 2006;Sakamoto and Cabrera 2003).…”
Section: Immune Response To E Granulosusmentioning
confidence: 99%
“…Increased Th1 responses (IFNγ or IL-12) impair PSC survival and cyst development, while IL-4 and IL-10 induce heavier cyst loads and impair PSC killing (Al-Qaoud and Abdel-Hafez 2008; Amri et al 2007Amri et al , 2009). Other mechanisms of immune evasion include polyclonal activation of B cells (Cox et al 1989) and induction of IL-10, IgG4, and high levels of nonspecific antibodies and lack of antibody avidity maturation, as shown experimentally by injection of carbohydrate fractions of PSC (Miguez et al 1996;Mourglia-Ettlin et al 2011a;Ferragut and Nieto 1996;Severi et al 1997;Baz et al 1999Baz et al , 2008Cardozo et al 2002;Dematteis et al 2001).…”
Section: Immune Response To E Granulosusmentioning
confidence: 99%